2017
DOI: 10.1002/brb3.836
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sphingolipids and depressive symptoms in coronary artery disease

Abstract: BackgroundDepression is highly prevalent in individuals with coronary artery disease (CAD) and increases the risk of future cardiac events and mortality. Sphingolipids have been implicated in the pathophysiology of both CAD and depression. This study assessed the association between plasma sphingolipid concentrations and depressive symptoms in CAD subjects.MethodsDepressive symptoms were measured using the depression subscale of the self‐reported Hospital Anxiety and Depression Scale (HADS). Sphingolipid conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 91 publications
(127 reference statements)
1
17
0
Order By: Relevance
“…These sphingolipids have been consistently associated with metabolic disease ( 35 ), psychiatric disorders ( 36 ), and neurodegenerative diseases ( 37 ). Our own studies have previously shown associations between these sphingolipids and depressive symptoms ( 38 ) and cognitive response to exercise in patient with CAD ( 17 ). As such, sphingolipids may be important markers of early pathophysiological changes in at-risk populations such as those with CAD.…”
Section: Discussionmentioning
confidence: 94%
“…These sphingolipids have been consistently associated with metabolic disease ( 35 ), psychiatric disorders ( 36 ), and neurodegenerative diseases ( 37 ). Our own studies have previously shown associations between these sphingolipids and depressive symptoms ( 38 ) and cognitive response to exercise in patient with CAD ( 17 ). As such, sphingolipids may be important markers of early pathophysiological changes in at-risk populations such as those with CAD.…”
Section: Discussionmentioning
confidence: 94%
“…For the PCs, “aa” indicates that both moieties at the sn-1 and sn2 positions are fatty acids and bound to the glycerol backbone via ester bonds—”ae” denotes that one of the moieties, either in the sn-1 or at sn-2 position, is a fatty alcohol and bound via an ether bond. Sphingolipids contain a sphingoid base attached to an acyl group such as a fatty acid (Dinoff et al 2017) and are the most common form of lipid in brain cell membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The balance between these two sphingolipids is referred to as the “sphingolipid-rheostat” as increased ceramide levels can initiate apoptosis and increased S1P concentrations generally promote cell survival and proliferation (van Brocklyn and Williams 2012). Previous studies have suggested that sphingolipid metabolism may be a potential novel therapeutic target in depression (Kornhuber et al 2005; Dinoff et al 2017), as higher circulating levels of ceramides C16:0, C18:0, C20:0, C24:1, and C26:1 (Gracia-Garcia et al 2011) and lower circulating levels of SMs have been reported in patients with MDD. In our study, ketamine induced a significant increase in circulating concentration of SMs in MDD patients relative to placebo, suggesting that ketamine may be having an effect on acid sphingomyelinase activity, and as a result decreasing circulating ceramide levels; however, further studies in this pathway are needed to confirm these findings.…”
Section: Arginine Pathwaymentioning
confidence: 99%
“…Similarly, plasma levels of several ceramide species, including Cer16:0, Cer18:0, Cer20:0, Cer24:1, and Cer26:1 but not Cer22:0 or Cer24:0, were increased in patients experiencing a major depressive episode during the past 2 years [9]. Higher plasma ceramide Cer16:0, Cer18:0, Cer20:0, Cer22:0, Cer24:0, and Cer24:1 levels were also observed in patients with MDD and bipolar disorder [10], and higher plasma levels of ceramide Cer16:0 and Cer18:0 and sphingomyelin SM18:1 were associated with the increased severity of depression symptoms in patients with coronary artery disease [11]. In contrast, plasma sphingomyelin SM26:1 [12], SM21:0 and SM21:1 [13] levels were decreased in MDD patients, and the SM23:1/SM16:0 ratio was negatively correlated with the severity of depressive symptoms in a Dutch family [14].…”
Section: Introductionmentioning
confidence: 96%